Optimalisasi Kinerja Archimedes Screw Menggunakan Sistem Transmisi Terhadap Output Daya (Watt) - Fikri, Fikri; Ramdhani, Dedy; Hasdiansah, Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Water energy sources at low head and discharge can be utilized as a generator of electrical energy, one of which is by using the Archimedes screw turbine, the Screw turbine is used in Pico Hydro Power Plants (PLPTH) as a small-scale power plant by utilizing water energy from river flow. The purpose of this research is to optimize the performance of the Archimedes screw turbine Pico Hydro Power Plant so as to produce a better power output. In this study the authors designed an Archimedes screw turbine model with a screw angle of 28°, 5 blade type screw, and 40° turbine tilt. This study focuses on a transmission system using a belt and pulley ratio of 1:3, with two levels of transmission, and a turbine tilt angle of 40°. The method used in this study is the experimental method. As a result, after trials were carried out on a stream located in the Sungailiat Archipelago Fishing Port area, the highest turbine rotation value was 146 rpm and generator rotation 756 rpm, resulting in a power output of 8 watts within 45 minutes of the trial period in the field. This means that after modifying the Archimedes screw turbine with the transmission system and the turbine tilt angle of 40°, the resulting power output increases.